To the mechanisms of effect of new complex plant remedy - V. G. Banzaraksheyev (Acta Biomedica Scientifica, 2012)
The object of study — complex plant remedy has been developed on the basis of Tibetan medicine recipes. Course preventive introduction of the phytoremedy decreases the formation of products of peroxidation and increases antioxidant capacity. One of the mechanisms underlying hypolipidemic action of phytoremedy is the inhibition of the processes of lipid peroxidation.